Daedalus in Jerusalem - Demsky, Aaron (The Biblical archaeology review, 2023)
A unique Hebrew inscription discovered in 2018 continues to excite epigraphers and historians of the Second Temple period. Dated to the Herodian period (late first century BCE-first century CE), it provides one of the first archaeologically attested full spellings of the name Yerushalayim (Jerusalem) as it is pronounced in Hebrew to this day.1 However, it […]